HISTORIC SPLENDOUR OF CHINESE MUSLIM ARTS AND CULTURE ON DISPLAY AT MGTF USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 August 2016 – Narrations and relations between the Islamic world and China in the stories and histories need to be documented, displayed and shared with everyone.